STRATEGI PENGEMBANGAN PENDIDIKAN MULTIKULTURAL DI INDONESIA - Elhefni Elhefni; Apri Wahyudi (Jurusan PGMI FTIK IAIN Metro Lampung, 2017)
Multicultural education needs to be nurtured both in formal and non-formal education because of Indonesia's cultural potential, tradition, and geographical environment, and demographics is remarkable. Education has a major role to play in promoting multicultural understanding. The cultivation of such understanding should be carried out as early as possible, so that it will continue to be constructed in the cognition of the child's sense of ownership and pride of the nation's culture until he grows up so that a democratic and egalitarian attitude will emerge to accept cultural diversity. To achieve that, the strategy of multicultural education development is needed. Multicultural education development strategies that can be undertaken, ie curriculum development, professional quality improvement of educational staff, development of education management systems, development of higher education system, equality of community perception, inculcation of recognition and appreciation of diversity (culture or culture, ethnicity, race, Religion, worldview and so on), avoiding views that assume that one group is superior to the other, and fosters and accustoms to a dialogical attitude.